Skin rash and mild bruising: Is montelukast a safe drug? - Deep Inder; Seema Manak; Faiz Akram; Pawan Kumar (Indian Journal of Respiratory Care, 2018)
Montelukast is one of the commonly used drugs in asthma patients. It is prescribed along with inhalational corticosteroids. Although a relatively safe drug, there is a probability of occurrence of skin rashes and skin bruising. Authors present a case report of a 64-year-old chronic asthmatic woman, reporting widespread erythematous eruptions with mild skin bruising and generalized pruritus mostly affecting her lower abdomen and upper extremities. The rash appeared 28 days after introduction of montelukast (10 mg OD). The physician excluded other attributable factors such as trauma, autoimmune disorders such as Churg-Strauss syndrome, and food allergy. Reappearance of rashes after montelukast introduction and complete resolution of the skin rashes after discontinuing it confirms montelukast as offending drug. Naranjo causality assessment score also revealed a “certain/definite” relationship to the montelukast. Long-term safety of montelukast needs to be reviewed by prescribing physicians to prevent adverse reaction.